UP E-PASA electronic portfolio and assessment management system - del Rosario, Joebet Isaac V.; Fabila, Joseph D.; Mohan, Francis Hans E.; Ramirez, Ma. Eden C. (2008.)
Electronic learning, the use of latest technology on education, offers a wide array of tools that may be used in improving current teaching techniques. The electronic portfolio is one of such tools. Currently, deliverables submitted by students of the Department of Computer Science are only submitted to teacher-in-charge. It is recommended that the department (or any institution of learning) use an electronic portfolio and assessment management system to enable them to assess students overall performance as opposed to performance on individual subjects, using the evidences of learning stored in the electronic portfolio. This paper describes the process of planning, implementing and testing of the said system. The system is currently deployed and being subjected to unit and integration tests to ensure quality. This system is highly valuable to any educational institution that seeks to improve its quality of instruction, as the information made available by the system may be used to modify current teaching techniques and curriculum. This can also help the student in the process of learning and help him showcase his best work to teachers, peers and future employers.
Thesis (B.S. Computer Science)--University of the Philippines, Diliman.
Keywords: Electronic portfolios in education; Internet in education; UP E-PASA.